1976
DOI: 10.1111/j.1529-8817.1976.tb02834.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF PIGMENT MUTANTS IN A BLUEGREEN ALGA, ANACYSTIS NIDULANS1

Abstract: SUMMARY Characteristics of 2 types of pigment mutants of the bluegreen alga, Anacystis nidulans, are described. “Yellow‐green” mutants (YG) which have normal chlorophyll but only half the phycocyanin of the parent are similar to the parent in number of reaction centers/cell, number of chlorophylls/reaction center, maximum turnover rate of the reaction centers, quantum yields at 620 and 686 nm and specific growth rate; they have a reduced action at 620 nm. “Blue” mutants (BL) with somewhat higher phycocyanin bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The ratio of RC II to phycobilisomes is determined to be 4.1 ± 1.3 for Neoagardhiella and 1.7 ± 0.5 for Anacystis (Table III). The RC II/phycobilisome ratio for Neoagardhiella is in good agreement with a value of 3 to 4 EF particles (putative RC II)/phycobilisome found for the red alga Grifflthsia pacflcia (23) and that for Anacystis is similar to an estimate of 1.1 RC II/phycobilisome (24).…”
supporting
confidence: 73%
“…The ratio of RC II to phycobilisomes is determined to be 4.1 ± 1.3 for Neoagardhiella and 1.7 ± 0.5 for Anacystis (Table III). The RC II/phycobilisome ratio for Neoagardhiella is in good agreement with a value of 3 to 4 EF particles (putative RC II)/phycobilisome found for the red alga Grifflthsia pacflcia (23) and that for Anacystis is similar to an estimate of 1.1 RC II/phycobilisome (24).…”
supporting
confidence: 73%
“…In PBsome-containing organisms it is generally assumed that the arrangement of the photosystems in the thylakoid is predictable from the PSII/phycobiliprotein ratio (6,7) and that the PBsome distribution on the stromal surface is indicative of the PSII location (8,9). Since PBsomes with PSII activity have been isolated, a direct functional association exists in vivo (10), although a direct interaction between PBsomes and PSI cannot be ruled out.…”
mentioning
confidence: 99%
“…The quantitative relationships between PSII and the PBsomes are still not clear. For example, recent quantitative studies of the RC and pigment content of red algae and cyanobacteria (10,25,28) have shown that the RCII:PBsome ratio is variable and can often be greater than unity. Furthermore, Diner (1) Woilman (29) have presented evidence that in the red alga Cyanidium caldarium about half of the RCII do not receive any of the light energy absorbed by the PBsomes.…”
mentioning
confidence: 99%